AB1128 An Evaluation of A Comic Book for Children Explaining Chronic Pain in Older Adults: A Qualitative Study of Older People's Views on the Value of "Medikidz Explain Pain". (10th June 2014) - Martin, D.; Anthony, G.; Anderson, L.; Schofield, P.; McNamee, P.; Jones, D.; Clarke, A.; Docking, R.; Smith, B.H.
Abstract : Background: Chronic pain is a particular problem for older adults: age-related biopsychosocial changes can make it more difficult to deal with the effects of chronic pain, and widely held views that living with pain is a natural consequence of aging can add to the problem. For many older people their role as a grandparent is a significant part of their life and this can be disrupted by chronic pain. As part of a large study on self management by older people with chronic pain (EOPIC) we developed a comic book to address an issue that older people highlighted as important to them: a lack of understanding by their grandchildren and other family members of how pain affects the older person. The comic book, "What's Up With Moira's Grandad? Medikidz Explain Chronic Pain", presents key information, including that gathered within the EOPIC study from interviews with older people about their experience of living with pain. The book was developed in partnership with Medikidz, in their specialist format of comic books of health information for children and younger people. Objectives: To explore older people's views on the value of the comic book. Methods: This is a qualitative study using semistructured interviews. Participants were older people over 65 years with self-reported chronic pain, living in the community, who were grandparents. Purposive sampling was used to recruit men and women from a range of ages. Participants were given a copy of the comic book to use at their discretion. They then took part in a face to face interview during which they discussed their thoughts on the value of the book in the context of their role as a grandparent. The interviews were audio recorded and transcribed. The transcripts were analysed thematically. Results: 13 people have been interviewed (6 women, 7 men; age range 63-87; range of duration of living with pain 3-30 years). Discussions described various degrees of disruptive effects of chronic pain on grandparenting, and understanding by young people and other family members of older people with chronic pain. Most participants were very positive about the potential of the book to facilitate young people's understanding about chronic pain and its effects in older people, highlighting issues including the attractiveness of the format, the authenticity of the story, and the comprehensive scope of the information. Conclusions: The comic book is a potentially useful resource to facilitate the understanding of younger people, and the wider family, about how chronic pain affects older adults. Acknowledgements: The study was supported by a grant from the Joint UK Research Council Lifelong Health and Wellbeing initiative. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3029